MAGDALENA: study protocol of a randomised, placebo-controlled trial on cognitive development at 2 years of age in children exposed to SSRI in utero. Issue 8 (5th August 2018) - Heinonen, Essi; Szymanska-von Schultz, Barbara; Kaldo, Viktor; Nasiell, Josefine; Andersson, Ewa; Bergmark, Mikaela; Blomdahl-Wetterholm, Margareta; Forsberg, Lisa; Forsell, Erik; Forsgren, Anna; Frööjd, Sandra; Goldman, Amy; et al.
Abstract : Introduction: Ten per cent of all pregnant women are depressed. Standard therapy of pregnant women with moderate depression is selective serotonin reuptakeinhibitors (SSRI). Observational studies on neurodevelopment after fetal SSRI exposure show conflicting results. Our primary objective is to compare the cognitive development in children exposed to sertraline and maternal depression with those exposed to maternal depression and placebo in utero. We hypothesise that there is a significant neurodevelopmental difference between the groups. As a secondary objective, we study the add-on effect of sertraline to internet-based cognitive behavioural therapy (ICBT) to treat moderate depression during pregnancy. Methods and analysis: MAGDALENA is a randomised, placebo-controlled, double-blinded trial in Stockholm Healthcare Region with 2.3 million inhabitants. The women are recruited in weeks 9–21 of pregnancy either through Antenatal Health Clinics or through social media. They are to be diagnosed with moderate depression without ongoing antidepressive therapy or any serious comorbidity. The women in the intervention arm receive sertraline combined with a 12-week period of ICBT; the control arm is treated with placebo and ICBT. We assess the cognitive development in the offspring at the age of 2 years using Bayley Scales of Infant and Toddler Development, third edition (BSID-III). We aim at recruiting 200 women, 100 women in each treatment arm, to ensure statistical power to detect a clinically relevant difference between the groups. Ethics and dissemination: This randomised trial will provide long-sought evidence about the effects of SSRI and maternal depression during pregnancy on the neurodevelopment in the offspring. The study is approved by the Regional Ethical Review Board at Karolinska Institutet in Stockholm and the Swedish Medical Products Agency. It is registered with the European Clinical Trials Database (EudraCT), Number: 2013-004444-31. Results will be disseminated at scientific conferences, published in peer-reviewed journals and made available to the public. Trial registration number: EudraCT2013-004444-31; Pre-results.